IS HYPOADIPONECTINEMY A RISK FACTOR FOR CORONARY ARTERY DISEASE? - Ozturk, U.; Karaca, I.; Yavuzkir, M.; Dagli, N.; Balin, M.; Polat, V.; Akbulut, H. (Elsevier Ireland Ltd, 2008)
[Abstract Not Available]